Estabilização de areia com adição de cal e cinza volante - Pinto, Salomão (1971)
Verify the behavior of a Brazilian fly ash as a stabilizing agent of a pure uniform sand. Timing at the action of fly ash, a soil with no cohesion, lacking of colloidal fraction, was chosen. This soil is not suitable for the usual processes of stabilization with portlant cement or lime. The fly ash - a residual material from the burning of pulverized coal - and lime, when wetted, presents a pozzolanic reaction and cements the sand grains. It was intended to confirm research work made abroad, by using a fly ash produced in a thermo-electric plant from the southern part of Brazil. It was taken into account the possibilities that this process might have, in the coastal region where sand dunes are present. The experimental results from laboratory are presented in tables and graphs, and are thereafter discussed. Three (3) mixtures were studied having: 10%, 17,5% and 25% fly ash, all of them with 6% hydrated lime. Two (2) different compaction energies were applied, and three (3) curing ages adopted: 7,14 and 28 days. It was also investigated the temperature effect on curing at: 7°C, 23°C, 40°C and 60°C for mixture having 17,5% fly ash. The unconfined compressive strengths obtained with the cylindrical specimens are comparable to those of soil-cement; at 28 days values were 37 kg/cm² and 54 kg/cm² for mixture with higher proportion of fly ash, at two compaction energies. It was observed the effect of curing time and temperature on the strength or on pozzolanic reaction. Furthermore, the results furnished information about the compaction parameters of mixtures with views to field use. Summing up these consideration it was put into evidence in laboratory the possibilities of this type of soil stabilization as it had already been done abroad. Above all it was shown the value of the fly ash produced in a thermo-electric plant of the southern part of Brazil in stabilizing sands which are typical of coastal dunes.